Relationship between school sports club membership and depressive symptoms among new recruits of the Japan Self-Defense Force: A longitudinal study - Tohru Kobayashi; Shigekazu Ukawa; Takashi Kimura; Koichi Shido; Akiko Tamakoshi (Journal of Physical Fitness and Sports Medicine, 2024)
The relationship between participation in extracurricular school club activities in adolescence and subsequent depressive state experiences in adulthood, after joining the workforce, is unclear. The present study aimed to explore this relationship in new recruits of the Japan Ground Self-Defense Force (JGSDF). In April 2013, 925 recruits of the JGSDF, all of whom were male and aged 18–27 years, were enrolled. Club activity status during high school was categorized as follows: participated in sports club, participated in nonsport club, or no club participation. Depressive symptoms were assessed with the 20-item version of the Center for Epidemiologic Studies Depression Scale (CES-D), at the baseline survey and a second survey conducted 2 months later, in June 2013. Analysis of covariance was used for association between club activity status and changes in CES-D scores. After a 2-month period, results showed a significantly higher average of CES-D score changes for participants in nonsport club activities (β = 3.90, 95% confidence interval = 2.22–6.71) or those with no club activities (β = 2.24, 95% confidence interval = 0.20–2.94), compared to those who participated in a sports club. These findings were adjusted for age, baseline CES-D score, regular exercise, smoking status, alcohol consumption, sleep duration, and breakfast habits. Recruits without a history of sports club participation may be at higher risk of developing depressive symptoms than those who participated in a sports club. Our results may be useful for the early detection of people who are susceptible to depression engaged in occupations such as the JDSF.